The Caribbean University- Innovation and Economic Development - Bhoendradatt, Tewarie (Revista Educación Superior y Sociedad (ESS), 2019)
Caribbean society needs an innovation-led Caribbean University system to achieve economic progress and sustainable development. The Caribbean University needs to have a sustainable economy and society surround it so that the business of the University can become viable and the fulfillment of its mandate more meaningful and satisfying. Forging a partnership among Caribbean Universities together with a corresponding partnership with the Government and Business might be the beginning of an innovative intervention to support an innovation driven sustainable development initiative for the Caribbean region.